Carbazole-based aggregation-induced phosphorescent emission-active gold(I) complexes with various phosphorescent mechanochromisms - Chen, Zhao; Deng, Xiao-Wen; Wang, Xiao-Yan; Wang, An-Qi; Luo, Wen-Tao (Frontiers in Chemistry, 2022)
Graphical Abstract